Environmental issues in the Mediterranean : processes and perspectives from the past and present - Wainwright, John, 1967- (Routledge studies in physical geography and environment, 2004)
The Mediterranean has been subject to changing human settlement and land use patterns for millennia. This book reviews both physical and social aspects of this region, in relation to its environment.